CLAP SWITCH TO CONTROL ROOM LIGHT - Estrada, Richie (Teknik dan Ilmu Komputer, 2012)
Lamp switch is a very important component of switching on or extinguish lights. In general, the system which is used to control lamps is still being manually switched on or off. The manual system control is often difficult for humans in terms of operations. This paper presents an automatic switch circuit as an alternative to manual switches. Automatic switch is used as a clapping sound control.Keywords : lamp, manual switch, automatic switch, control, clapping sound